Investigation of the Changes in Maxillary and Mandibular Morphology and Dentoalveolar Structures with Open Bite Treatment - Bülent Baydaş; Asiye Kuyumcu; İbrahim Yavuz; İsmail Ceylan (Turkish Journal of Orthodontics, 2005)

(untitled)
The purpose of this study is to examine the changes that occur in the maxillary and mandibular morphology and dentoalveolar structures as a result of the correction of open bite cases by fixed orthodontic treatments. The study consists of a total of 20 subjects' pre-and post-treatment lateral cephalometric films, 14 females and 6 males with skeletal open bite, who were treated with extraction of four premolars by using Edgewise technique and anterior vertical elastics. To determine the significance levels of the changes resulting from the treatment, the pre-and post-treatment measurements were compared by means of the paired t-test. In addition, descriptive statistical data containing the mean and standard deviations were determined separately for the pre and post treatment periods. It was determined in the present study that axial inclinations of the upper incisors and lower molars were uprighted. The evaluation of dentoalveolar heights showed that only upper posterior region remained stable and that there was a certain increase in the lower and upper anterior and lower posterior dentoalveolar heights. Besides, significant increases were observed in all of the area measurements made in the maxillary, mandibular and symphysis regions. In the soft tissues, however, no significant changes resulting from the treatment were observed except Ricketts upper lip measurement. With these results in mind, it was reported that open bite treatment was rather much realized with the extrusion of incisors.